Critical Thinking Analysis Based on Imagination Games in Listening Poetry - Helmi Wicaksono (EDUCATIO : Journal of Education, 2022)
This study aims to identify critical thinking based on the game of imagination in listening to poetry. This type of research is descriptive qualitative research. The dat a collectiontechnique uses the technique of a written test. TheH asil obtained is as follows. (1) the characteristics of critical thinking are found in the application of indicators, namely identifyingtheimagination of information from the title of the poem being listened to, interpreting the imagination of the poem array being listened to, understanding the imagination of each verse of the poem being listened to, and assessing the results of the imagination of the meaning of the poem. (2) The teacher's efforts in improvingthe ability to think kritis students are based on imagination games in listening to poetry. (3) Obstacles faced by students in developing critical thinking skills are lack of focus and lack of calm.